2016
DOI: 10.1177/0306624x16667572
|View full text |Cite
|
Sign up to set email alerts
|

A Gender-Responsive Treatment Facility in Correctional Services: The Development of Psychological Gymnasium for Women Offenders

Abstract: With increasing evidence suggesting a disparity in female and male offenders in terms of rehabilitative needs, growing concern has been placed on the development of gender-specific services for female offenders. As such, a prison-based psychological gymnasium (PSY GYM), with distinctive features in integrating cognitive-behavioral and positive-psychology concepts to address female offenders' needs, was set up in 2011. The present study aims to introduce the concept as well as present findings to evaluate the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The study showed that, as cognitive self-schemas, character strengths can be defined as strategies, beliefs, and personal assets (Padesky & Mooney, 2012), which cause changes on negative and positive sides; however, the CBT and positive psychology intervention (PPI) literature do not show a close integration. A newly developed intervention called prison-based psychological gymnasium was set in 2011; this program fused CBT with PPI to address female offenders’ needs, and the results indicated significant reduction in their negative emotions (e.g., depression, anxiety, and stress) and remarkable increase in their positive sense (e.g., hope and gratitude; Mak, Ho, Kwong, & Li, 2016). However, this initial trial targeted at a special group.…”
mentioning
confidence: 99%
“…The study showed that, as cognitive self-schemas, character strengths can be defined as strategies, beliefs, and personal assets (Padesky & Mooney, 2012), which cause changes on negative and positive sides; however, the CBT and positive psychology intervention (PPI) literature do not show a close integration. A newly developed intervention called prison-based psychological gymnasium was set in 2011; this program fused CBT with PPI to address female offenders’ needs, and the results indicated significant reduction in their negative emotions (e.g., depression, anxiety, and stress) and remarkable increase in their positive sense (e.g., hope and gratitude; Mak, Ho, Kwong, & Li, 2016). However, this initial trial targeted at a special group.…”
mentioning
confidence: 99%